Analisis Manajemen Risiko Pada Tabungan Berhadiah Emas Di BPRS Sarana Prima Mandiri Pamekasan - Iqbal Rafiqi; Abd Wahid (CV. ITTC INDONESIA, 2024)
Saving Account with gold prizes at BPRS Sarana Prima Mandiri Pamekasan is very attractive to customers because the prizes are in the form of gold. It’s become an advantage for the bank considering the large number of customers who take part in the program. but besides that, the large amount of funds collected from these savings can also be a risk to the bank if the bank cannot manage it well. so that, a good risk management is needed so that banks can avoid risks that can harm the bank. This research uses qualitative research method with approach of case study. The results of this research study is the application of risk management in the management of prize savings at BPRS SPM Pamekasan is carried out by: 1) Risk identification by conducting 5C analysis and also BI Checking for customers who wish to do financing, 2) Measuring risk by providing value to customers before making a decision, 3) Risk monitoring by conducting periodic evaluations, 4) Risk control is usually carried out for customers with problems, namely by billing, giving warning letters and ending guarantee auctions.